Analysis of Language Mistakes in Ad Writing on Instagram - Nur Raudhoturrahmah; Amay Lanjar Wulandari; Hasnah Faizah (International Forum of Researchers and Lecturers, 2026)
This study aims to describe the forms of language errors in writing ads on Instagram. The research is motivated by the fact that there are still many uses of Indonesian that are not in accordance with the rules in captions and promotional texts on social media. The research uses a qualitative approach with a descriptive method. The research data was in the form of words, phrases, clauses, and sentences that contained language errors in Instagram ad uploads from 20 active business accounts during the January-March 2026 period. Data collection techniques are carried out through listening, documentation, and recording techniques. The data was analyzed based on the General Guidelines for Indonesian Spelling (PUEBI) and the Great Dictionary of Indonesian Language (KBBI). The results of the study showed that there were language errors consisting of spelling errors, morphological errors, syntactic errors, and semantic errors. The dominant errors include the use of non-standard words, capital letter writing errors, punctuation omissions, the use of foreign terms, the omission of affixes, ineffective sentence structure, and ambiguity of meaning. The factors that cause language errors are influenced by the use of informal language, practical digital communication habits, and lack of understanding of the rules of the Indonesian language. This research is expected to increase the awareness of social media users in using good and correct Indonesian, especially in writing digital advertisements so that the message conveyed is more effective, communicative, and professional.